Kinerja Pembiayaan UMKM Terhadap Profitabilitas Bank Umum Syariah di Indonesia - Marwah Nur Al-Zauqi; Iwan Setiawan (Journal of Applied Islamic Economics and Finance, 2020)
This study aims to determine how MSME financing and Capital Adequacy affect the profits of Islamic commercial banks. This study uses a quantitative approach that analyze secondary data from statistic of Islamic Bank in Indonesia period 2016-2019. The analysis used multiple linear regression analysis methods. Data processing uses eviews program. The results of this study indicate that MSME financing has a significant positive effect on Return on Asset. Capital Adequacy Ratio has a significant positive effect on Return on Asset. MSME financing and Capital Adequacy Ratio has a simultant effect to Return on Asset. The results of this study are expected to be a material consideration for Islamic commercial banks in providing MSME financing and maintaining capital adequacy.